Relationship between indexed aortic area and aortic diameter in bicuspid aortic valve aortopathy: A retrospective cohort study. (May 2021) - Acharya, Metesh; Valencia, Oswaldo; Edsell, Mark; Tome, Maite; Morgan, Robert; Nowell, Justin; Jahangiri, Marjan
Abstract: Background: Aortic dissection is a life-threatening complication of bicuspid aortic valve (BAV)-associated aortopathy. In these populations, whilst prophylactic replacement of proximal thoracic aortic aneurysms (TAAs) is generally recommended at threshold diameters ≥5.5 cm, dissection may occur in smaller aortas. An alternative size-based parameter, the cross-sectional aortic area/patient height ratio (indexed aortic area, IAA), correlates with increased dissection risk at abnormal values > 10 cm 2 /m. We sought to assess the utility of the IAA in identifying at-risk BAV-associated TAAs with abnormal IAA, albeit with sub-threshold aortic diameter. Materials and methods: We retrospectively identified 69 patients with BAV-associated TAAs who underwent surgical repair between 2010 and 2016. Aortic diameter was measured on pre-operative imaging, and IAA calculated, at the mid-sinus of Valsalva, sino-tubular junction and mid-ascending aorta for each patient. We determined proportions of aneurysms with IAA >10 cm 2 /m, median IAAs corresponding to aortic diameters <4.0 cm, 4.0–4.5 cm, 4.5–5.0 cm, 5.0–5.5 cm and >5.5 cm, and median aortic diameters corresponding to an abnormal IAA. Results: 50.9%, 12.5% and 64.6% of aneurysms at the sinus of Valsalva, sino-tubular junction and mid-ascending aorta, respectively, had an abnormal IAA. 51.9% and 88.9% of patients with aortic diameter 4.5–5.0 cm and 5.0–5.5 cm, respectively, had an abnormal IAA. In aneurysms with abnormal IAA involving the sinus of Valsalva, sino-tubular junction, and mid-ascending aorta, median aortic diameters were 4.98 cm, 5.04 cm and 5.11 cm, respectively. Overall, 57/72 (79.2%) at-risk aneurysms with IAA >10 cm 2 /m had diameters smaller than the 5.5 cm guideline cut-off for surgical intervention. Conclusion: Significant proportions of BAV-associated TAAs are at increased risk of aortic dissection attending an IAA >10 cm 2 /m, whilst not fulfilling the size criteria indicating aortic surgery in contemporary guidelines. Further analysis of IAA in larger BAV cohorts is necessary to clarify its role in patient selection and optimal timing for prophylactic aortic replacement. Graphical abstract: Image 1 Highlights: Indexed aortic area is an alternative validated parameter of aortic dimensions. Significant proportions of aortic aneurysms associated with a bicuspid aortic valve have abnormal indexed aortic areas. Abnormal indexed aortic areas first emerge at diameters 4.5-5.0 cm, smaller than the 5.5 cm threshold for surgery. Many at-risk aneurysms may thus not meet size criteria for surgical intervention. In this series, over 79% of at-risk aneurysms had diameter <5.5 cm.